ANALISIS TINGKAT KEPUASAN MASYARAKAT TERHADAP KUALITAS PELAYANAN PADA KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BOGOR - Adyas, Dasmansyah; Fahrudin, Achmad (Economicus, 2020)
The purpose of this study was to determine the level of performance / quality of service and the level of community expectations in Disdukcapil Bogor Regency .Data analysis uses the IBb(Importance-Peformance Analysis) method. The results of the study show that: (1) The level of service quality which is the top priority and must be carried out in accordance with the expectations of the community is an indicator that is in quadrants A and B including: provisions, completation of the maintenance process on time. (2) The level of expectation or satisfaction of the community which is considered less important is the indicator that is in quadrant C, including: Service personnel having expertise in their fields,service officer in Disdukcapil are responsive to community complaints, service oficers pay attention to the community served and Officers do not ask for fees wild to the community. Whereas quadrant D is an indicator that is considered less important but the community feels satisfied so that it is considered excessive, including: Requirements and service procedures at Disdukcapil do not confuse the public, officers are always at the service and there is AC in the waiting room for services. (3). Overall the expectation or satisfaction of the community towards the service quality performance of the Bogor Regency Disdukcapil still has not 100% .